Membrane feeding of dengue patient’s blood as a substitute for direct skin feeding in studying Aedes-dengue virus interaction - Tan, Cheong-Huat (2016)
Background: Understanding the interaction between Aedes vectors and dengue viruses (DENV) has significant implications in determining the transmission dynamics of dengue. The absence of an animal model and ethical concerns regarding direct feeding of mosquitoes on patients has resulted in most infection studies using blood meals spiked with laboratory-cultured DENV. Data obtained from such studies may not reflect the natural human-mosquito transmission scenario. This study explored the potential of using membrane feeding of dengue patient’s blood as a substitute for direct skin feeding.